Acute and subacute effects of resistance training with and without blood flow restriction on muscle thickness and cytokines - Evangelista,Alexandre L. (2019)
It was our objective to verify the time course of muscle thickness and cytokine concentration after a resistance training session. In one of the experimental conditions, the training session was performed with low load (20% 1RM) and restriction of blood flow. In the other experimental condition, the same training was performed with high load (80% 1RM) and without blood flow restriction. Femoral rectus muscle, vastus lateralis, brachial biceps and triceps brachii muscle thickness and the serum cytokine dosage were analyzed pré, 0h, 24h and 48h after the training sessions. For the upper and lower limbs, the main results showed significant (p< 0.05) effect on time for the thickness in all muscle but not (p> 0.05) to experimental condition. To cytokines concentrations, a significant (p= 0.004) interaction between the time and conduction for IL10. Conversely, there was no difference between the weeks (p= 0.698) or time (p= 0.142) in the means of TNF. In conclusion both experimental conductions promoted similar changes on muscular swelling without alterations on TNFa, however, the RST protocol induced increase on IL-10 concentration after 24 hours of exercise session.